Deskripsi Pemecahan Masalah Matematika berdasarkan Langkah Polya ditinjau dari Kepribadian Siswa Tipe Melankolis - Razak, Firdha; Sutrisno, Ahmad Budi; Kamaruddin, Rahmat (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
This research is a qualitative research aimed to disclose math problem-solving ability based on Polya steps on SPLDVâ€™s materialÂ in term of student personalities melancholy (ME). Instruments used for this research are : 1) personality test is usedÂ to categorize the students based on their personality, 2) math problem-solving test is used to showÂ students’ ability in solving mathematical problems based on Polya steps, and 3) guided interview is contained guidelines aim to clarify answers and trace the process of studentsâ€™ thought in depth. Data are collected by test and interviewÂ and analyzed by using Miles and Hubermanâ€™s data analysis. The research processes are: (a) formulated the indicators based on math problem-solving on Polya steps (b) formulated a valid and reliable instrument (personality test, math problem-solving task and guided interview) (c) collected the subject by providing personality type, (d) collected data to show the description of math problem-solving is done by the students, (e) did time triangulation to get valid data, (f) performed data analysis problem-solving based on personality types, (g) conducted a discussion of the results of analysis, (h) drew conclusions of the research. The results showed the subject of melancholy did the Polya steps in problem-solving, which are (1) understand the problem (2) plan a settlement (3) settle a plan (4) check back.